Microplastics influence the functional responses of a tropical estuarine calanoid Pseudodiaptomus annandalei - Sharma, Jaigopal; Rai, Malayaj; Guino-o, Robert S. (Frontiers in Ecology and Evolution, 2024)
Being chemically inert and morphologically similar (< 5 mm in size) to the natural prey of copepods, microplastics (MP) affect them through entanglement, ingestion, and interfering with their natural prey selection. The effect of external factors such as MP can be observed in the form of alterations in the functional and numerical responses of copepods. The functional response is explained as the relationship between the intake rate of a consumer and the amount of food available in particular ecotope. Holling (1959) considered three types of functional response- (i) with increasing food density when intake rate increases linearly until asymptote, called as Type-I functional response, (ii) when proportion of prey ingested by the consumer decreases monotonically with prey density, considered as type-II functional response (Smith and Smith, 2020), and (iii) when ingestion rate and food density shows a sigmoid relationship, is considered as type-III functional response (Iyer and Rao, 1996). In the present study we attempt to elucidate the effects of MP on functional responses of brackish water, demersal, calanoid copepod- Pseudodiaptomus annandalei feeding on the rotifer, Brachionus rotundiformis and the ciliate, Frontonia microstoma. Ability of P. annandalei to survive environmental fluctuations and its nutritional value make it an ecologically important organism in the estuarine ecosystem. The experiment for estimation of functional response included four setups with adult and copepodite stage of P. annandalei in each with six replicates at six different prey densities, in presence and in absence of MP particles. Without MPs P. annandalei showed typical Type-II functional response, where proportion of prey consumed significantly declined with increasing prey density. Whereas, in MP applied medium the proportion of prey consumed did not exhibit significant relationship with initial prey density. Number of ciliate and rotifer ingested by copepodites and adults were significantly lower in MP contaminated medium than with prey either monospecific or in combination with microalgae. Due to comparable size of MP to the prey species and unspecialized feeding of P. annandalei in natural waters, we hypothesize reduced predation rates as a result of pseudo satiation resulting from MP ingestion leading to malnutrition and MP storage in copepod biomass.